Regioselective copper-catalyzed oxidative coupling of α-alkylated styrenes with tertiary alkyl radicals - Wang, Cong (2020)
A radical-mediated oxidative cross-coupling of readily accessible α-alkylated styrenes with 1,3-dicarbonyl compounds utilizing a combination of Cu(OAc)2 and air as a catalytic system is described. Rather than requiring α-halocarbonyl compounds, this efficient approach enables direct installation of tertiary functionalized alkyl motifs to olefins with simple carbonyl derivatives. The novel protocol is characterized with high allylic selectivities via a competing β-H elimination. Both radical-clock and -trapping experiments provided clear-cut evidence for the intermediacy of an α-keto carbon-centered radical.